Acryl-3,5-bis(2,4-difluorobenzylidene)-4-piperidone targeting cellular JUN proto-oncogene, AP-1 transcription factor subunit inhibits head and neck squamous cell carcinoma progression - Levi Arnold; Juan Pineda Gomez; Michael Barry; Marrion Yap; Laura Jackson; Thuc Ly; David Standing; Subhash B. Padhye; Bernhard Biersack; Shrikant Anant; Sufi Mary Thomas (Open Exploration Publishing Inc., 2023)
Aim: Head and neck squamous cell carcinoma (HNSCC) is the seventh most common cancer worldwide with a survival rate below fifty percent. Addressing meager therapeutic options, a series of small molecule inhibitors were screened for antitumor efficacy. The most potent analog, acryl-3,5-bis(2,4-difluorobenzylidene)-4-piperidone (DiFiD; A-DiFiD), demonstrated strong cellular JUN proto-oncogene, activator protein 1 (AP-1) transcription factor subunit (JUN, c-Jun) antagonism. c-Jun, an oncogenic transcription factor, promotes cancer progression, invasion, and adhesion; high (JUN) mRNA expression correlates with poorer HNSCC survival. Methods: Four new small molecules were generated for cytotoxicity screening in HNSCC cell lines. A-DiFiD-treated HNSCC cells were assessed for cytotoxicity, colony formation, invasion, migration, and adhesion. Dot blot array was used to identify targets. Phospho-c-Jun (p-c-Jun) expression was analyzed using immunoblotting. The Cancer Genome Atlas (TCGA) head and neck cancer datasets were utilized to determine overall patient survival. The Clinical Proteomic Tumor Analysis Consortium (CPTAC) datasets interfaced with University of Alabama at Birmingham Cancer Data Analysis Portal (UALCAN) were analyzed to determine protein levels of c-Jun in HNSCC patients and correlate levels with patient. Results: Of the small molecules tested, A-DiFiD was the most potent in HNSCC lines, while demonstrating low half-maximal drug inhibitory concentration (IC50) in non-malignant Het-1A cells. Additionally, A-DiFiD abrogated cell invasion, migration, and colony formation. Phospho-kinase in vitro array demonstrated A-DiFiD reduced p-c-Jun. Likewise, a time dependent reduction in p-c-Jun was observed starting at 3 min post A-DiFiD treatment. TCGA Firehose Legacy vs. recurrent and metastatic head and neck cancer reveal a nearly 3% DNA amplification in recurrent/metastatic tumor compared to below 1% in primary tumors that had no lymph node metastasis. CPTAC analysis show higher tumor c-Jun levels compared to normal. Patients with high JUN expression had significantly reduced 3-year survival. Conclusions: A-DiFiD targets c-Jun, a clinical HNSCC driver, with potent anti-tumor effects.